Aspectos socioeconômicos dos batedores de açaí dos municípios de Macapá e Santana no estado do Amapá -AP. - Lidiane de Vilhena Amanajás Miranda; Sérgio Barbosa de Miranda; Viviane Vanessa de Vilhena Amanajás (Confins)
The açai beaters represents açai processing and sale points known as açai kneading machines or beers. This class occurs in a diffuse way in all the peripheries of the municipalities of the North of Brazil. The name "açai batter" comes from the handling of an electric machine for the extraction of the açai drink. The methodology used to obtain the data was the direct collection technique, through the semi structured forms, which were submitted and approved by the Ethics Committee of the Federal University of Amapá. This research aims to carry out a socioeconomic diagnosis of the açai batters of the municipalities of Macapá and Santana in the state of Amapá. In the results, it was observed that 57.9% (n=212) of the açai batsmen are active in the activity over two years, a reality that indicates that these açai batters have already developed and present a planning structure in the function performed, considerable experience with the practice. However, at the same time, 42.1% are açai batters with less than two years of activity time, it means that the market still accepts new entrants in this activity, that is, a market not yet fully exploited. From the group 68.4% of the beaters obtained açai from their main source of income, and 31.6% of the respondents carried out another activity to complement their incomes. It was also detected the little concern and the low investment in courses of preparation or qualification to carry out the activity in the mixers, outlining a predominantly artisanal and informal activity.